Clinical outcome of endonasal endoscopic prelacrimal approach in managing different maxillary pathologies - Lin, Yu Hsuan (PeerJ, 2020)
BACKGROUND: The aim of the study was to evaluate the treatment outcomes of endoscopic prelacrimal recess approaches (EPLAs) in managing different sinus pathologies, analyzing associated adverse events and post-treatment quality-of-life. METHODS: We enrolled 21 consecutive patients (22 lesions) who received endoscopic sinus surgical procedures with EPLAs in two tertiary medical institutes between 2015 and 2018. Quality-of-life and self-rated symptom severity data were collected using the 22-item Sino-Nasal Outcomes Test (SNOT-22) and 10-point visual analog scales (VAS), respectively. RESULTS: A total of 21 patients (mean age (standard deviation) 51.7 (14.5) years; 16(76.2%) male) were followed up for 12.7 months. The most common symptoms were nasal discharge and nasal airway obstructions. Nine lesions (40.9%) were sinonasal papilloma’s, seven lesions were other types of neoplasms (31.8%; five benign and two malignant), two were trauma-related (9.1%), and four inflammatory diseases (18.2%). Patients with non-papilloma lesions had higher presurgical SNOT-22 than those with papillomas (P-value = 0.021). After EPLAs, non-papilloma patients had significant improvements in SNOT-22 and VAS (P-values = 0.012 and 0.012, respectively), while those with papillomas had only marginally significant improvements in VAS (P-value = 0.061). The most common adverse events was temporary cheek/tooth numbness (n = 11), and patients with sinonasal papillomas were more likely to have post-treatment complications than those with other disease entities. CONCLUSIONS: EPLAs were found to effectively manage various sinus diseases. Short-term life-quality improvements were promising. Future large-scale studies with longer follow-up periods are recommended.